Integrated Pharmacy Research and Practice - Todd A; Ling J (Dove Medical Press, 2012)
Adam Todd,1 Jonathan Ling21Wolfson Research Institute, School of Medicine and Health, Queen’s Campus, Durham University, Stockton-on-Tees, UK; 2Faculty of Applied Sciences, University of Sunderland, Sunderland, UKBy 2014, the worldwide annual spend on medicines is expected to exceed one trillion dollars, representing an increase of nearly 90% since 2005.1 Thanks to modern medicine and the expanding number of pharmaceutical agents used to treat a wide range of diseases, average life expectancy is also set to increase, with, for example, average life expectancy in the UK increasing to 80 years of age, which is eight years higher than in the 1970s.2 However, despite this success, people around the world fail to use their medicines as they should, with a recent report by the World Health Organization estimating that, in developed countries, around 50% of patients are noncompliant with their long-term medication.3 In developing countries, this percentage is even higher, which is of particular concern because infectious diseases, such as human immunodeficiency virus and tuberculosis, are spreading rapidly. In view of this, the concept of "pharmaceutical care" has been introduced, and is defined as "the responsible provision of drug therapy for the purpose of achieving definite outcomes that improve (or maintain) a patient’s quality of life".4